2020
DOI: 10.1080/2162402x.2020.1851539
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI cell tracking of immune cell recruitment to tumors and draining lymph nodes in response to anti-PD-1 and a DPX-based immunotherapy

Abstract: DPX is a unique T cell activating formulation that generates robust immune responses (both clinically and preclinically) which can be tailored to various cancers via the use of tumor-specific antigens and adjuvants. While DPX-based immunotherapies may act complementary with checkpoint inhibitors, combination therapy is not always easily predictable based on individual therapeutic responses. Optimizing these combinations can be improved by understanding the mechanism of action underlying the individual therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…The smallest immune cells (5-7µm), CD8 + T cells, which also have lower phagocytic activity, had much lower iron loading when labelled with MEs (0.22-0.3pg/cell, both MLRs) compared to SPIO (3pg). These results correspond well with other literature indicating average cell loading of 3-5pg iron/cell when using SPIO 9,30 . This level of iron loading in the MEs is typically on the low end of detectability in MRI cell tracking (ideally > 0.5pg/cell) indicating that MEs may not be an optimal choice for this cell type, or that if they are used, more invasive methods of labelling may be necessary, such as transporation and transfection agents.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The smallest immune cells (5-7µm), CD8 + T cells, which also have lower phagocytic activity, had much lower iron loading when labelled with MEs (0.22-0.3pg/cell, both MLRs) compared to SPIO (3pg). These results correspond well with other literature indicating average cell loading of 3-5pg iron/cell when using SPIO 9,30 . This level of iron loading in the MEs is typically on the low end of detectability in MRI cell tracking (ideally > 0.5pg/cell) indicating that MEs may not be an optimal choice for this cell type, or that if they are used, more invasive methods of labelling may be necessary, such as transporation and transfection agents.…”
Section: Discussionsupporting
confidence: 92%
“…The number of SPIO-labelled MDSCs was stable over the 8-day period (Fig. 5a), which is consistent with SPIO degradation rates seen anecdotally in our lab and in previous studies 9,10 . Interestingly, the number of MElabelled MDSCs was also stable over time and consistently higher than the number of SPIO-labelled MDSCs present.…”
Section: In Vivo Tracking Of Me-labelled Mdscssupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, immunotherapy has been manifested to gradually become an integral component of cancer therapy [ 13 ]. Studies have revealed that analysing the characteristics of TME, especially immune cell infiltration, can improve the understanding of the likelihood of immunotherapeutic response or survival [ 14 ]. In recent years, owing to the emergence of novel immunotherapy strategies involving PD-1 and PD-L1 and the clinical efficacy of PD-1 and PD-L1 blockade in various solid cancers, blocking of the PD-1 and PD-L1 pathways has emerged as an effective strategy for cancer treatment [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tremblay et al used MRI technology to quantitatively track cytotoxic T lymphocytes (CTLs) and myeloid cells (MLCs) labeled with superparamagnetic iron oxide nanoparticles (SPIO) in vitro. 75 The results showed that these quantitative molecular MRI techniques can be extended to the study of various cancers and immunotherapy combinations, thereby deepening the understanding of longitudinal immunological changes and their mechanisms. Dekaban et al reviewed the use of MRI technology to track the migration of dendritic cells (DCs) labeled with iron oxide nanoparticles in vitro.…”
mentioning
confidence: 99%